Differences of virulence factors, and antimicrobial susceptibility according to phylogenetic group in uropathogenic Escherichia coli strains isolated from Korean patients - Miri Hyun; Ji Yeon Lee; Hyun ah Kim (BMC, 2021)
Abstract Background Escherichia coli is among the most common uropathogens. Increased antibiotic resistance in Gram negative bacilli is global concern. Alternative therapeutic options including vaccines against uropathogenic E. coli (UPEC) have been developed. In this study, we compared the genotypic characteristics and antimicrobial susceptibility of UPEC according to phylogenetic groups. Methods We retrospectively reviewed the medical records of pyelonephritis patients with UPEC between February 2015 and June 2018. The study was conducted at a medical center in Korea. We compared the clinical and genotypic characteristics of UPEC according to phylogenetic groups. The phylogenetic groups and 29 virulence factors were identified using multiplex polymerase chain reaction. Results Phylogenetic group analysis revealed that most uropathogenic E. coli belonged to groups B2 and D: B2 (276, 77.7%), D (62, 17.5%), B1 (12, 3.4%), and A (5, 1.4%). Among the virulence factors, fyuA, fimH, traT, iutA, papG allele II, and papC were the most frequently observed. Phylogenetic group B2 was more closely related to virulence factors, including fimH, sfa/focED, focG, hlyA, cnf1, fyuA, and PAI, than group D. Groups B2 and D showed similar clinical presentations and complications. Group B2 had mostly healthcare-associated infections and antimicrobial resistance. Group D mostly had community-acquired infections. The K1 serotype was prevalent in group B2, and K5 was the most prevalent in group D. Conclusions Phylogenetic group B2 had more proportions and types of virulence factors than group D. Group B2 showed a high presentation of virulence factors related to adhesions and toxins. An increased presentation of antimicrobial resistance and healthcare-associated infections was also noted. Considering the genetic characteristics of UPEC, alternative therapeutic options targeting frequent virulence factors might be considered in addition to antibiotics.